El Imaginario Ciudadano de la Procesión del Señor del Buen Suceso en la Identidad Cultural de Riobamba Periodo Enero-Junio 2017 - Terán Zavala., Estephaníe Carolina (2019)
The investigation '' The Imaginary Citizen of the Procession Lord of Good Success in the Cultural Identity of Riobamba period January - June 2017 '' was carried out in order to analyze the perception of the inhabitants of Riobamba, in terms of the imaginary as a generator of cultural identity in this event that takes place every year on Holy Tuesday, taking into account that this effigy has 369 years of existence together with the story that manifests a miraculous story, founding the "Slave Society", who carry the image throughout its path. This event is considered a tradition that comes from the ancient Riobamba, considered a space of devotion, celebration, reminder of the passion and death of Jesus. The use of two age groups has been considered, in which young people and adults are involved in order to know their perception of the event, concepts were used to establish the theoretical framework, theories of communication, population surveys, interviews with experts in the topic, interview to the citizenship making a field investigation. In this way it is concluded that the Procession of the Lord of Good Success is present in the imaginary of the inhabitants of the city of Riobamba because it generates cultural identity for the image and the characters of the Procession among the most common, the Cucuruchos and Roman soldiers, allowing that the citizens become participants and get involved in this kind of acts of the catholic religion, reliving this tradition year after year.